ChemInform Abstract: Nonstoichiometric Perovskite CaMnO3‐δ for Oxygen Electrocatalysis with High Activity. Issue 42 (14th October 2014) - Du, Jing; Zhang, Tianran; Cheng, Fangyi; Chu, Wangsheng; Wu, Ziyu; Chen, Jun
Abstract Nonstoichiometric CaMnO3‐δ (0 < δ ≤ 0.5) is prepared by thermal reduction of pristine perovskite microspheres and nanoparticles, obtained by thermal decomposition of carbonate precursors and the Pechini route, respectively.